Comparison of Clinical, Ultrasound, and Electrophysiologic Changes in Chronic Inflammatory Demyelinating Polyneuropathy: A Prospective Study. Issue 3 (6th March 2023) - Okhovat, Ali Asghar; Nafissi, Shahriar; Moradi, Kamyar; Ziaadini, Bentolhoda; Panahi, Akram; Haghi Ashtiani, Bahram; Fatehi, Farzad
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: The follow-up and monitoring of response to immunomodulatory therapy in patients with chronic inflammatory demyelinating polyneuropathy are still challenging. Various outcome measures have been proposed in recent years, and some are now frequently used in daily clinical practice; however, reliable biomarkers for the disease activity and treatment response are lacking. Methods: Cross-sectional nerve area of the bilateral vagus, fifth and the sixth cervical spinal, median, ulnar, tibial, peroneal, and sural nerves were measured at 2 time points with an interval of 6 months using nerve ultrasound. The results were used to calculate the ultrasound pattern sumscore (UPSS). The correlation between UPSS change (ΔUPSS) and changes in functional and nerve conduction studies measures over the study period were assessed. Results: Sixteen patients completed this prospective, observational study. General linear model showed that ΔUPSS is significantly associated with ΔMedical Research Council sumscore (β = −0.72, P = 0.003), Δhandgrip strength (β = −0.57, P = 0.014), ΔRasch-built overall disability scale (β = −0.57, P = 0.010), and Δoverall neuropathy limitations scale (β = 0.75, P < 0.001), after adjustment of confounding variables. Nevertheless, ΔUPSS was not correlated with other clinical measures, including Δpinch power, Δ9-hole peg test, Δ10-m walking test, and Δnerve conduction study sumscore ( P values > 0.05). Conclusions: Nerve ultrasound might be an efficient method for monitoring the functional status of patients with chronic inflammatory demyelinating polyneuropathy over time because the alterations in its scores could significantly reflect clinical changes.